New feather mites of the subfamily Pterodectinae (Acari: Astigmata: Proctophyllodidae) from passerines (Aves: Passeriformes) in Mato Grosso do Sul, Brazil - Mironov, Sergey V.; Literak, Ivan; Čapek, Miroslav (Zootaxa, 2008)
Four new species of the genus Pterodectes Robin, 1877 and three new monotypic genera of the feather mite subfamily Pterodectinae (Astigmata: Proctophyllodidae) are described from various passerines captured in Mato Grosso do Sul (Brazil). The following new species are described: Pterodectes paroariae sp. n. from Paroaria capitata (Orbigney et Lafresnaye, 1837) (Emberizidae), P. tangarae sp. n. from Tangara cayana (Linnaeus, 1766) (Thraupidae), P. molothrus sp. n. from Molothrus bonariensis (Gmelin, 1789) (Icteridae), P. pitangi sp. n. from Pitangus sulphuratus (Linnaeus, 1766) (Tyrannidae), Tyrannidectes berlai gen. n., sp. n. from Myiarchus tyrannulus (Muller, 1776) (type host) and M. ferox (Gmelin, 1789) (Tyrannidae), Metapterodectes furnarius gen. n., sp. n. from Furnarius rufus (Gmelin, 1788) (Furnariidae), and Nanodectes formicivorae gen. n., sp. n. from Formicivora rufa (Thamnophilidae). Brief comments on the taxonomic structure of the subfamily Pterodectinae and species content of the genus Pterodectes are given. The two newly described genera, Tyrannidectes gen. n. and Metapterodectes gen. n., are close to the genus Pterodectes. The genus Tyrannidectes gen. n. differs from the latter genus by loss of setae sR on trochanters III, and Metapterodectes gen. n. differs by loss of setae sR on trochanters III and Solenidion σ 1 on genua III. In Pterodectes, setae sRIII and solenidion σ 1 are present on legs III. The genus Nanodectes gen. n. is close to Proterothrix Gaud, 1968 and differs from that genus by the loss of idiosomal setae d1, d2, e2, f2 that is a unique combination of lost setae among all pterodectines; in closely related Proterothrix, only idiosomal setae c1 may be absent.